Analysis of the Effectiveness of Distribution of Zakat Funds at Baznas of North Sumatra Province - Marliyah Marliyah; Putri Ayuni Sari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
It is important to measure the effectiveness in distributing zakat in order to know the capacity in managing zakat, especially in the distribution of zakat funds. This study aims to determine the effectiveness of the distribution of zakat funds at BAZNAS, North Sumatra Province. This research is a qualitative research. Data analysis was carried out with a descriptive approach which was equipped with a study of relevant literature and documentation. Measurement of the effectiveness of zakat distribution is carried out using the Allocation to Collection Ratio (ACR) formula in the Zakat Core Principle Model. The data is sourced from the financial statements of BAZNAS of North Sumatra Province related to the amount of collection and distribution of zakat funds in the 2018-2020 period. The results showed that the level of effectiveness of zakat distribution in BAZNAS North Sumatra Province for the last three years, namely in 2018-2020 was 68.91% which was included in the Fairly Effective category or quite effective with an average collection of 7,049,004,839 and an average distribution 4,857,647,660. Thus, BAZNAS of North Sumatra Province has a fairly good capacity in the distribution of zakat funds.